A Stochastic Analysis of Investment Prospects in West Africa: A Case of Ghana and Nigeria - Anane-Agyemang, M (University of Ghana, 2015)
The main aim of this study is to analyse investment prospect in Ghana and Nigeria using rate of inflation, 90-day Treasury bill rate (interest rate) and local currency per US dollar exchange rate. The dataset span from January, 2003 to June, 2014. Stochastic time series analyses (ARIMA and ARCH-type) models were employed in the forecasting of the macroeconomic variables and simple investment accumulation was also employed in the accumulation of investment returns. The results revealed that forecasting rate of inflation would best be done using the ARIMA(1,1,2) –ARCH(2) model for Ghana and ARIMA(0,1,1)-ARCH(3) model for Nigeria. Treasury bill rate would best be modeled by ARIMA(1,1,2)-ARCH(1) for Ghana and ARIMA(0,1,1)-ARCH(3) for Nigeria. Again, forecasting exchange rate in Ghana was best done using the ARIMA(0,2,4)-ARCH(1) and that of Nigeria was ARIMA(0,1,1)-ARCH(1,1). The results also revealed an upward trend in the forecast of rate of inflation, interest rate and local currency per US dollar exchange rate for both Ghana and Nigeria. Furthermore, the results showed that investment in Ghana is worth more than investment in Nigeria since the accumulated value of investment return in Ghana grew faster than that of Nigeria for both the case of zero inflation and that of varying inflation in the two economies. Also based on the results, it would be prudent to spend return in Nigeria than in Ghana since the rate of inflation in Ghana grows faster than that of Nigeria and hence making cost of living in Ghana relatively higher than that of Nigeria.
Thesis (MPhil) - University of Ghana, 2015